Pengaruh Brand Image, Brand Trust dan Electronic Word of Mouth terhadap Keputusan Pembelian Produk Skincare Lokal Emina Melalui Online Influencer Marketing sebagai Mediasi pada Gen Z di Kota Denpasar - Alya Dina Oktavia; I Gede Fery Surya Tapa; Putu Dyah Permatha korry; Ida Bagus Teddy Prianthara (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
The rapid growth of the beauty industry in Indonesia has intensified competition among local skincare brands, encouraging companies to strengthen marketing strategies that align with the digital behavior of Generation Z consumers. This study aims to analyze the influence of brand image, brand trust, and electronic word of mouth (e-WOM) on purchasing decisions of local skincare product Emina, with online influencer marketing as a mediating variable among Generation Z consumers in Denpasar City. This research employed a quantitative approach using data collected from 220 respondents selected through purposive sampling, consisting of Generation Z consumers who actively use social media and have purchased Emina products more than twice. Data analysis was conducted using Structural Equation Modeling Partial Least Squares (SEM-PLS) to examine both direct and indirect relationships among variables. The results indicate that brand image, brand trust, electronic word of mouth, and online influencer marketing have positive and significant effects on purchasing decisions. Furthermore, online influencer marketing was proven to partially mediate the relationship between brand image, brand trust, and e-WOM toward purchasing decisions. The findings highlight the strategic role of influencers in strengthening consumer perceptions and trust, ultimately enhancing purchase decisions among digitally active Gen Z consumers. This study contributes theoretically to digital marketing and consumer behavior literature while providing practical implications for local skincare companies in designing effective social media based marketing strategies.